Sosialisasi Edukasi serta Pentingnya Konservasi Geodiversity Kepada Masyarakat Desa Jari - Indriani, Yulia; Fadilah, Rifqo’ Nur; Aji Prayogo, Dimas Priyo; Saprita, Riri; Endriani, Diah (Universitas Pahlawan Tuanku Tambusai, 2025)
A community service activity through educational outreach on geodiversity conservation was conducted in Jari Village, Gondang District, Bojonegoro Regency, East Java. Jari Village has two potential geosites: the